To noč sem jo videl in Ob nastanku sveta Draga Jančarja ter pojem literatura spominjanja - Leskovec, Andrea (Ars et humanitas, 2024)
n important theme in Slovenian literature after 2010 is confrontation with the Se-cond World War and the post-war socio-political discourses. This kind of literature could be called memory literature, where the focus is less on the subjective perspective of memory and more on the function of this literature, which is, among other things, to reflect the discourses of memory. This function can be subversive or stabilising, me-aning that this kind of literature influences and helps shape socio-political and histori-cal discourses. This is also the case with the novels To noč sem jo videl and Ob nastanku sveta, which deal with the Second World War and the post-war period, thematising not only the war as such, but also the related socio-political discourse of the post-war period and the present, which is characterised by ideological polarisation. Not even the discourse of literary science is exempt from this polarization, where – as in the literary works themselves – conflicting cultural memories confront each other. There AH_2024_1_FINAL.indd 37AH_2024_1_FINAL.indd 378. 10. 2024 07:50:548. 10. 2024 07:50:54 AndreA Leskovec / TonočsemjovideLinobnAsTAnkusveTA drAgA jAnčArjATerpojemLiTerATurAspominjAnjA38are at least two reasons for this. On the one hand, there is the politico-ideologically motivated question of power. The second reason is that at first sight, the novels repro-duce and reinforce established social narratives, which links them to social reality and makes them relatively easy to instrumentalise. However, the analysis shows that the novels attempt to break down standardised and homogenising concepts of the past.
Keywords: druga svetovna vojna; družbeni narativi; Jančar, Drago; literatura in spomin; literature and memory; Slovene literature; slovenska književnost; social narratives; World War II